Exploring Health Workers’ Perspectives on Barriers to Family Planning Service Delivery: A Study in Health Center of District 2, Marikina City - Rodina P. Fernandez; Ma. Kryssie G. Fernandez; Jervie C. Dual; Leprex L. Padre; Claudine F. Payacag (Future Science / FSH-PH Publications, 2026)
This study examined the barriers to family planning (FP) service delivery as perceived by health workers in selected health centers in District 2, Marikina City. The study is anchored on the WHO Health Systems Framework (WHO, 2007) and the Socio-Ecological Model (Bronfenbrenner, 1979), which explain how systemic, organizational, and socio-cultural factors interact to influence health service delivery. Specifically, it identified organizational, technical, resource-related, and socio-cultural factors that influence the implementation of FP programs and explored strategies to improve service delivery. A descriptive quantitative research design was employed, utilizing a structured self-administered questionnaire distributed to health workers involved in FP service provision. Data were analyzed using descriptive statistics, including frequency, percentage, and weighted mean, with limited qualitative inputs from respondents’ perspectives used to support interpretation of the results. Findings revealed that organizational challenges such as staffing shortages, high workload, and policy-related issues significantly affected FP service delivery. Technical and resource-related barriers included inconsistent supply of contraceptives, limited training opportunities, and inadequate infrastructure. Socio-cultural factors, particularly misconceptions about FP methods, cultural beliefs, and religious influences, were also perceived as major barriers to FP utilization among clients. Despite these challenges, health workers identified capacity-building activities, improved supply chain management, strengthened community education, and sustained policy support as key strategies for enhancing FP service delivery.